A silica/PVA adhesive hybrid material with high transparency, thermostability and mechanical strength. Issue 5 (12th January 2017) - Pingan, Hu; Mengjun, Jia; Yanyan, Zuo; Ling, He
Abstract : Silica/PVA hybrids containing over 50 wt% silica were prepared, exhibiting high transmittance, Young's modulus, thermostability, adhesive strength and hygrothermal resistance. Abstract : A cross-linked silica and polyvinyl alcohol (PVA) hybrid material was prepared via a sol–gel process for use as a highly transparent, thermostable and mechanically strong coating. The effect of the H2 O/TEOS ratio on the properties of the silica/PVA hybrid films, such as transmittance, thermal stability, mechanical strength, adhesive strength and hygrothermal resistance, is discussed herein. A strong chemical interaction between PVA and silica is indicated by the weakening of the C–OH peak and the formation of a Si–O–C peak in the XPS results. This interaction is further confirmed by the decrease in the PVA crystallinity from 23.29% to 2.56%, and the reduction in the silica/PVA melting point from 204.3 °C to 122.0 °C. This excellent compatibility between PVA and silica makes silica/PVA disperse well in solution with a dendritic-like or spherical morphology, and leads to a 97% increase in visible light transmittance. Therefore, compared with pure PVA, the obtained silica/PVA hybrid films are transparent. Even though the mass percentage of silica in the material is beyond 50 wt%, its Young's modulus is much improved from 0.17 ± 0.03 GPa to 2.52 ± 0.10 GPa, its ultimate tensile strength is enhanced from 40.1 ± 9.27 MPa to 80.3 ± 2.5 MPa, and its adhesive strength is increased from 475 N (1.52 MPa) to 712 ± 90 N (2.29 MPa) and it can almost maintain super hygrothermal resistance after 15 hygrothermal aging cycles. It is believed that the obtained silica/PVA hybrid could be used as a high-performance coating with excellent transparency, thermostability and mechanical strength.